Melatonin ameliorates chronic renal failure-induced oxidative organ damage in rats - (:unkn) unknown (BLACKWELL MUNKSGAARD, 2004)
Chronic renal failure (CRF) is associated with oxidative stress that promotes production of reactive oxygen species (ROS). Melatonin, the chief secretory product of the pineal gland, was recently found to be a potent free radical scavenger and antioxidant. The aim of this study was to examine the role of melatonin in protecting the aorta, heart, corpus cavernosum, lung, diaphragm, and kidney tissues against oxidative damage in a rat model of CRF, which was induced by five of six nephrectomy. Male Wistar albino rats were randomly assigned to either the CRF group or the sham-operated control group, which had received saline or melatonin (10 mg/kg, i.p.) for 4 wk. CRF was evaluated by serum blood urea nitrogen (BUN) level and creatinine measurements. Aorta and corporeal tissues were used for contractility studies, or stored along with heart, lung, diaphragm, and kidney tissues for the measurement of malondialdehyde (MDA, an index of lipid peroxidation), protein carbonylation (PC, an index for protein oxidation), and glutathione (GSH) levels (a key antioxidant). Plasma MDA, PC, and GSH levels and erythrocytic superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities were studied to evaluate the changes of antioxidant status in CRF. In the CRF group, the contraction and the relaxation of aorta and corpus cavernosum samples decreased significantly compared with controls (P < 0.05-0.001). Melatonin treatment of the CRF group restored these responses. In the CRF group, there were significant increases in tissue MDA and PC levels in all tissues with marked reductions in GSH levels compared with controls (P < 0.05-0.001). In the plasma, while MDA and PC levels increased, GSH, SOD, CAT, and GSH-Px activities were reduced. Melatonin treatment reversed these effects as well. In this study, the increase in MDA and PC levels and the concomitant decrease in GSH levels of tissues and plasma and also SOD, CAT, GSH-Px activities of plasma demonstrate the role of oxidative mechanisms in CRF-induced tissue damage, and melatonin, via its free radical scavenging and antioxidant properties, ameliorates oxidative organ injury. CRF-induced dysfunction of the aorta and corpus cavernosum of rats was reversed by melatonin treatment. Thus, supplementing CRF patients with adjuvant therapy of melatonin may have some benefit.
Keywords: chronic renal failure; melatonin; oxidative damage; ERYTHROCYTE GLUTATHIONE-PEROXIDASE; INDUCED LIPID-PEROXIDATION; ERECTILE DYSFUNCTION; NITRIC-OXIDE; SUPEROXIDE-DISMUTASE; REACTIVE OXYGEN; BRAIN-REGIONS; FREE-RADICALS; IN-VITRO; STRESS